East Timor case study in international aid - Garner, Simon; Tilson, Leigh; Video Education Australasia (Australia : Video Education Australasia, 2003)
This program examines the aims, objectives and examples of aid work being done by International Aid organisations such as: Oxfam Community Aid Abroad, IDSS, AusAID, the Salesian order, and the Kiwanis. The introduction to East Timor's history is given-including the arrival of the Portugese and the Indonesian invasion
Title from title screen
Executive producer, Mark McAuliffe ; camera, Leigh Tilson ; editor, Leigh Tilson, Michael Henry
Middle - Senior Secondary
DVD Format
Keywords: Economic assistance; Economic assistance -- International cooperation